Web Intelligence-An Emerging vertical of Artificial Intelligence (International Journal of Engineering and Computer Science, 2014)
The information footprints of a rapidly increasing influx of internet users present us with an immense source of information that ultimately contributes to the construction of innovative web technology suitable for the future generations. Likewise, WEB INTELLIGENCE has been presented as the usage of advanced techniques in ARTIFICIAL INTELLIGENCE and INFORMATION TECHNOLOGY for the purpose of exploring, analyzing, and extracting knowledge from web data. Web Intelligence is the particular field of research and development to explore the fundamental roles as well as practical applications of artificial intelligence which is slowly developing throughout the world in order to create next generation of products, services and frameworks based on internet.